2012
DOI: 10.1589/jpts.24.1007
|View full text |Cite
|
Sign up to set email alerts
|

Core Stabilization Exercise Improves Pain Intensity, Functional Disability and Trunk Muscle Activity of Patients with Clinical Lumbar Instability:a Pilot Randomized Controlled Study

Abstract: Abstract. [Purpose] To determine the therapeutic effects of core stabilization exercise in the treatment of patients with clinical lumbar instability.[Methods] Twenty subjects with clinical lumbar instability were randomly assigned to a treatment or control group. The treatment group received 10 weeks of core stabilization exercise (CSE), while the control group (CG) received 10 weeks of hydrocollator therapy and trunk stretching exercises. Pain intensity of the instability catch sign (ICS), functional disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…After light skin abrasion and alcohol cleansing, four pairs of electrodes were placed over the right side of four trunk muscles: TrA and IO, RA, LM, and iliocostalis lumborum pars thoracis (ICLT). Details of electrode placement were consistent with a previous study 10. The ground electrodes of the right RA and ICLT muscles were placed over the ribcage, and the other two ground electrodes of the right TrA and IO and LM muscles were placed over the right iliac crest.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…After light skin abrasion and alcohol cleansing, four pairs of electrodes were placed over the right side of four trunk muscles: TrA and IO, RA, LM, and iliocostalis lumborum pars thoracis (ICLT). Details of electrode placement were consistent with a previous study 10. The ground electrodes of the right RA and ICLT muscles were placed over the ribcage, and the other two ground electrodes of the right TrA and IO and LM muscles were placed over the right iliac crest.…”
Section: Methodsmentioning
confidence: 89%
“…Details of this exercise have been described in our previous study (see supplementary material) 10. The 10-week exercise program was divided into three phases.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study indicated a reduction in pain and disability in both treatment groups (20). Nonetheless, the ratio activation of transversus abdominis and internal oblique relative to rectus abdominis was improved in subjects who were treated with CORE stability exercises (20). These exercises increase the activation capacity of segmental muscles and decrease pain in individuals with chronic nonspecific low back pain (20).…”
Section: Discussionmentioning
confidence: 82%
“…These findings corroborate with our study, in which this variable decreased from 6.60 ± 1.75 to 2.60 ± 2.32 points six months after intervention. A randomized controlled trial conducted by Areeudomwong et al (20) evaluated the effect of a 10-week CORE exercise program on pain, disability, and activation of trunk muscles in individuals with clinical instability of the lumbar spine. The results of this study indicated a reduction in pain and disability in both treatment groups (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation